differentiate the following y= e^(4x+1)*(x+1)^2 y= e^(-4x)square root (x+1), x>-1 y= X^4 e^-2x y= (1/x)e^x (x^2 + 2x + 2)e^-x Thanks
Follow Math Help Forum on Facebook and Google+
catch words: chain and product rule good luck
i can do the basic ones, i just can't do these ones in particular
Originally Posted by chaneliman differentiate the following y= e^(4x+1)*(x+1)^2 Use product and chain rules: y= e^(-4x)square root (x+1), x>-1 Again, use product and chain rules: y= X^4 e^-2x Again, use product and chain rules: y= (1/x)e^x Apply quotient rule: (x^2 + 2x + 2)e^-x Use product and chain rules: Thanks Does this make sense? --Chris
View Tag Cloud